A survey for variable young stars with small telescopes – IV. Rotation periods of YSOs in IC 5070. Issue 4 (21st July 2021) - Froebrich, Dirk; Derezea, Efthymia; Scholz, Aleks; Eislöffel, Jochen; Vanaverbeke, Siegfried; Kume, Alfred; Herbert, Carys; Campbell-White, Justyn; Miller, Niall; Stecklum, Bringfried; Makin, Sally V; Urtly, Thomas; et al.
ABSTRACT: Studying rotational variability of young stars is enabling us to investigate a multitude of properties of young star-disc systems. We utilize high cadence, multiwavelength optical time series data from the Hunting Outbursting Young Stars citizen science project to identify periodic variables in the Pelican Nebula (IC 5070). A double blind study using nine different period-finding algorithms was conducted and a sample of 59 periodic variables was identified. We find that a combination of four period finding algorithms can achieve a completeness of 85 per cent and a contamination of 30 per cent in identifying periods in inhomogeneous data sets. The best performing methods are periodograms that rely on fitting a sine curve. Utilizing Gaia  EDR3 data, we have identified an unbiased sample of 40 periodic young stellar objects (YSOs), without using any colour or magnitude selections. With a 98.9 per cent probability, we can exclude a homogeneous YSO period distribution. Instead, we find a bi-modal distribution with peaks at 3 and 8 d. The sample has a disc fraction of 50 per cent, and its statistical properties are in agreement with other similarly aged YSOs populations. In particular, we confirm that the presence of the disc is linked to predominantly slow rotation and find a probability of 4.8 × 10 −3 that the observed relation between period and presence of a disc has occurred by chance. In our sample of periodic variables, we also find pulsating giants, an eclipsing binary, and potential YSOs in the foreground of IC 5070.